2007
DOI: 10.4161/cc.6.12.4302
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Induces Apoptosis Through JNK/Bax-Dependent Pathway in Differentiated, but not Naïve PC12 Cells

Abstract: Differentiated PC12 cells have been used widely as a model for the analysis of neuronal degeneration. Some evidences showed that differentiated PC12 cells were more sensitive than naïve PC12 against apoptosis stimuli. However, the apoptosis mechanism of both types of PC12 cells was not fully known. In this study, the signaling pathways involved in tumor necrosis factor-a (TNFa)-induced apoptosis in living differentiated and naïve PC12 cells were investigated using confocal microscope for the first time. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…The cell death provoked by 0.2 μM staurosporine progressed more rapidly over time in differentiated PC12 cells than in undifferentiated cells ( Figure 1B). Therefore, our findings are in agreement with those recently reported by Zhang and colleagues (Oberdoerster and Rabin, 1999;Zhang et al, 2007), but not with those reported by Ekshyyan and Aw (Ekshyyan et al, 2005). Ekshyyan and Aw demonstrated that the transition of undifferentiated PC12 cells into differentiated cells affords protection against oxidative stress.…”
Section: Staurosporine Induces Cell Death To a Great Extent In Neuronsupporting
confidence: 91%
See 3 more Smart Citations
“…The cell death provoked by 0.2 μM staurosporine progressed more rapidly over time in differentiated PC12 cells than in undifferentiated cells ( Figure 1B). Therefore, our findings are in agreement with those recently reported by Zhang and colleagues (Oberdoerster and Rabin, 1999;Zhang et al, 2007), but not with those reported by Ekshyyan and Aw (Ekshyyan et al, 2005). Ekshyyan and Aw demonstrated that the transition of undifferentiated PC12 cells into differentiated cells affords protection against oxidative stress.…”
Section: Staurosporine Induces Cell Death To a Great Extent In Neuronsupporting
confidence: 91%
“…Several controversial reports show that neurotoxic effect was different between undifferentiated and differentiated phenotypes of PC12 cells (Oberdoerster and Rabin, 1999;Okouchi et al, 2005;Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, the pretreatment of cells with JNK inhibitor SP600125 decreased cisplatin induced activation of c-Jun phosphorylation but increased Bax expression and subsequent apoptotic cell death. It is known that participation of Bax in apoptosis occurs via protein expression level and conformational changes, cleavage and translocation to mitochondria (Okuno et al, 2004;Zhang et al, 2007). The results obtained by us prove that cisplatin-induced JNK signaling in adipocytes may influence Bax expression regulation and that JNK is an upstream Bax regulator.…”
Section: Discussionsupporting
confidence: 56%